2017
DOI: 10.1007/s10266-017-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemerin and its receptors, ChemR23 and CCRL2, in gingival tissues with healthy and periodontitis

Abstract: Chemerin is a chemoattractant protein that directs inflammatory cells that express its receptor chemokine receptor-like 1 (ChemR23) towards sites of inflammation. C-C chemokine receptor-like 2 (CCRL2), is the other receptor of chemerin, improves the interaction between chemerin and ChemR23. The aim of this study was to evaluate the expression of chemerin and its receptors in gingival tissues with healthy and periodontitis. Tissue biopsy samples were obtained from 20 patients with chronic periodontitis and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
0
11
0
3
Order By: Relevance
“…Chemerin was first identified as a novel retinoid-responsive gene in psoriatic skin lesions [ 80 ]. In addition to skin, chemerin is widely expressed throughout the human body and is mainly produced by the liver, WAT, and placenta [ 70 ] but is also found in the brain, spinal cord, spleen, lymph node, thymus, stomach, small intestine, colon, kidneys, testis, ovary, pituitary, lungs, heart, skeletal muscle, pancreas, arteries, cartilage, or gingival tissues [ 74 , 81 , 82 , 83 , 84 , 85 , 86 ]. The adipose tissue production of chemerin and CMKLR1 receptor in humans and mice was described in 2007, when chemerin came to be considered a new adipokine [ 87 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…Chemerin was first identified as a novel retinoid-responsive gene in psoriatic skin lesions [ 80 ]. In addition to skin, chemerin is widely expressed throughout the human body and is mainly produced by the liver, WAT, and placenta [ 70 ] but is also found in the brain, spinal cord, spleen, lymph node, thymus, stomach, small intestine, colon, kidneys, testis, ovary, pituitary, lungs, heart, skeletal muscle, pancreas, arteries, cartilage, or gingival tissues [ 74 , 81 , 82 , 83 , 84 , 85 , 86 ]. The adipose tissue production of chemerin and CMKLR1 receptor in humans and mice was described in 2007, when chemerin came to be considered a new adipokine [ 87 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…Oral ulcers are characterized by the inflammatory reactions of mucosal epithelial tissues in the oral cavity. During this process, chemokines, chemokine receptors and immune cells will all increase significantly ( 50 , 51 ). Therefore, the abnormal expression of the gene CCRL2 in mucosal tissues is very likely to trigger inflammation and then induce the occurrence of oral ulcers, and m6A-SNPs play an important role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Chemerin is also believed to be associated with a variety of chronic inflammatory conditions. Furthermore, some researchers have reported that chemerin and its receptors ChemR23 are expressed in periodontal tissues 18,35–37 . To elucidate the mechanism of action of chemerin, we knocked down ChemR23 in cementoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some researchers have reported that chemerin and its receptors ChemR23 are expressed in periodontal tissues. 18,[35][36][37] To elucidate the mechanism of action of chemerin, we knocked down ChemR23 in cementoblasts. Unlike virus-mediated methods, transfection approaches using LipoHigh cannot induce permanently stable gene silencing; however, we were able to verify the changes in protein expression via Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%